Implementasi MQTT Broker dengan Kemampuan Auto Scaling pada Internet of Things - Kevin Jonathan Harnanta; Adhitya Bhawiyuga; Achmad Basuki (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Internet of Things is a topic of discussion that is growing rapidly now. One protocol commonly used in communication between IoT devices is MQTT. In communication, these devices are interconnected with brokers MQTT. But along with the growth of IoT devices that make connection requests to MQTT brokers, MQTT brokers have decreased resources, and become a single point of failure. Therefore we need MQTT brokers who are able to have auto scaling capabilities so they can adapt to the growing demand for connections from IoT devices. In its implementation, MQTT broker is placed in a container and orchestrated with kubernetes so that it has the ability to auto scaling. In testing, a comparison is made between MQTT brokers with auto scaling capability and without auto scaling capability. Testing is done by measuring the maximum number of clients that can be connected, and the number of connections lost at the time the test is running. As a result, MQTT brokers with auto scaling capabilities can receive connection requests from clients 27% better than MQTT brokers without auto scaling capabilities. Whereas in measuring the number of disconnected connections, MQTT broker with auto scaling capability is able to provide 54.42% fewer disconnected connections than MQTT broker without auto scaling capability.